2010
DOI: 10.1007/s10343-010-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of winter wheat cultivars to wheat ear insects in Central Germany

Abstract: the intensity of thrips and wheat blossom midges (WbM) infestations in twelve wheat cultivars was evaluated at the Plant breeding Station, Silstedt, central germany in 2008 & 2009 growing crop seasons. the research aimed at selecting the least infested cultivar to be profitably used in the forthcoming cultivation. Infestation levels were studied in flowering and milky stages (GS 65 and 73) of each cultivar in every single-spikelet in sample of 10 ears in both years.There were significant differences in thrips … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Chavalle et al (2017) showed that 17 of 64 winter wheat cultivars registered for commercial use in Belgium were resistant to wheat midge, including the Aigle, Barok, Bodecor, Boregar, Farandole, Gallixe, Kundera, KWS Smart, Popeye, Lyrik, Reflection, Renan, Rubisko, Sherlock, Sy Epson, Tobak, and Universal cultivars. Other resistant cultivars reported in Europe include the German winter wheat cultivar, Skalmeje (Gaafar et al 2011), and the Scottish winter wheat cultivar, Lear (Chavalle et al 2015b). Sun et al (1998) and Shi et al (2002) concluded that phenolic acid played a significant role in the resistance of Chinese winter wheat cultivars.…”
Section: Crop Resistancementioning
confidence: 99%
“…Chavalle et al (2017) showed that 17 of 64 winter wheat cultivars registered for commercial use in Belgium were resistant to wheat midge, including the Aigle, Barok, Bodecor, Boregar, Farandole, Gallixe, Kundera, KWS Smart, Popeye, Lyrik, Reflection, Renan, Rubisko, Sherlock, Sy Epson, Tobak, and Universal cultivars. Other resistant cultivars reported in Europe include the German winter wheat cultivar, Skalmeje (Gaafar et al 2011), and the Scottish winter wheat cultivar, Lear (Chavalle et al 2015b). Sun et al (1998) and Shi et al (2002) concluded that phenolic acid played a significant role in the resistance of Chinese winter wheat cultivars.…”
Section: Crop Resistancementioning
confidence: 99%
“…The orange wheat blossom midge (OWBM), Sitodiplosis mosellana Géhin (Diptera: Cecidomyiidae), is an economically important pest and has caused serious yield losses in most wheat-growing areas worldwide ( Berzonsky et al 2002 ; Thomas et al 2005 ; Bruce et al 2007 ; Gaafar et al 2011 ; Gong et al 2013 ; Jacquemin et al 2014 ). Larvae feed on young kernels, causing kernel damage, poor seed quality, and lower yield.…”
Section: Introductionmentioning
confidence: 99%
“…OWBM has been recorded as a pest in most temperate wheat-growing areas of the world, but particularly in Europe, North America, West Asia, and the Far East (Duan et al 2013;Lamb et al 1999;Oakley et al 1998). In Europe, outbreaks of the OWBM were observed in recent years in the United Kingdom (Bruce et al 2007;Oakley 1994), France (Flodrops and Taupin 2010), Belgium (Jacquemin et al 2014), and Germany (Basedow and Gillich 1982;Gaafar et al 2011;Wetzel et al 1982). In Europe, outbreaks of the OWBM were observed in recent years in the United Kingdom (Bruce et al 2007;Oakley 1994), France (Flodrops and Taupin 2010), Belgium (Jacquemin et al 2014), and Germany (Basedow and Gillich 1982;Gaafar et al 2011;Wetzel et al 1982).…”
Section: Introductionmentioning
confidence: 99%